2020
DOI: 10.3177/jnsv.66.s336
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Turmeric against Bisphenol-A Induced Genotoxicity in Rats

Abstract: In this study, the protective role of turmeric on genotoxic effects of Bisphenol-A exposure in Wistar rats by in vivo experiment were investigated. Bisphenol-A is a known endocrine disruptor and suspected carcinogen, that comes diet through plastics for food packaging and food processing. In this study, rats were divided into three groups of twelve animals each and were administered with Bisphenol-A by oral gavage with levels of 0, 50 and, 100 mg. Half of the animals in each group were fed with feed which cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The very low concentrations of BPA caused toxic effects via affecting the physiological and biochemical parameters in multiple tissues of fish. Also, Panpatil et al [ 68 ] found that the BPA-treated groups exhibited significantly higher mean levels of damage in the liver and kidney as compared to the untreated control group. Furthermore, Pan et al [ 69 ] found that BPA declined sperm chromatin integrity while increased damage in mouse spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The very low concentrations of BPA caused toxic effects via affecting the physiological and biochemical parameters in multiple tissues of fish. Also, Panpatil et al [ 68 ] found that the BPA-treated groups exhibited significantly higher mean levels of damage in the liver and kidney as compared to the untreated control group. Furthermore, Pan et al [ 69 ] found that BPA declined sperm chromatin integrity while increased damage in mouse spermatogenic cells.…”
Section: Discussionmentioning
confidence: 99%
“…After a screening for the reliability and relevance of the results, six studies from four publications, all ranked as of limited relevance, were selected for further consideration (Figure 3 and Table 15 ). Of these, three studies were considered positive for the induction of MN and CA in the same publication (Tiwari et al, 2012 ) or of MN (Panpatil et al, 2020 [RefID 379‐G]) in rats following daily oral BPA administrations for 6 and 28 days, respectively. Tiwari et al ( 2012 ) applied a range of doses from 2.4 μg up to 50 mg/kg bw per day.…”
Section: Assessmentmentioning
confidence: 99%
“…In a separate publication, the same authors (Tiwari and Vanage, 2017 ) reported that these experimental conditions were associated with the induction of lipid peroxidation (malonaldehyde, MDA) and oxidative stress (decreased SOD, CAT, GSH) in rat bone marrow and peripheral blood lymphocytes. In Panpatil et al ( 2020 ) [RefID 379‐G], the dose range was much lower (50 and 100 μg/kg bw per day). A fourth study tested positive in the mouse bone marrow MN test after the administration of a daily dose of 50 mg/kg bw for 28 days in the presence of high level of cytotoxicity (Fawzy et al, 2018 [RefID 270‐G]).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study that investigated the protective effects of turmeric against BPA exposure-induced genotoxicity in Wistar NIN rats revealed that turmeric treatment decreased serum malondialdehyde and urinary 8-hydroxy-2′-deoxyguanosine levels. In addition, turmeric co-administration decreased the formation of micronuclei and DNA migration in hepatic and renal tissues [ 342 ]. Curcumin has been shown to reduce BPA-induced oxidative stress and histopathological alterations in Wistar rats’ testis and cardiac tissues [ 343 , 344 ].…”
Section: Various Natural Products That Are Effective Against Bpa-indu...mentioning
confidence: 99%